Study on Hearing Status of Elderly Patients attending a Specialized ENT Hospital (SAHIC) (Bangladesh Journal of Otorhinolaryngology, 2016)
Background: Age related hearing loss is a natural process in elderly population all over the world.Objectives: To determine the hearing level of elderly patients in relation to age, sex, socioeconomic condition and to determine the pattern and extent of hearing loss in old age.Method: This cross sectional study was carried out at out patient department of Specialized ENT Hospital of SAHIC, Mohakhali, Dhaka, from October 2012 to March 2013. 200 patients were included with age > 50 years and who have no past history of drug therapy. Data were collected by detailed history, clinical examination and audiometric findings and result were expressed in table form.Result: 57% patients were found with normal hearing and 43% had variable degree of hearing impairment. Highest number of hearing impairment was found in 9th decade. Most of hearing loss were found to be bilateral and sensorineural in type.Conclusion: A good number of elderly people in our country is suffering from some degree of hearing loss, which are mostly sensorineural in type. The prevalence and severity of hearing loss increases with increasing age.Bangladesh J Otorhinolaryngol; October 2015; 21(2): 80-84